2021
DOI: 10.3389/fnins.2020.605697
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Identification of Suicidal Risk in Patients With Schizophrenia Using Multi-Level Resting-State fMRI Features

Abstract: BackgroundSome studies suggest that as much as 40% of all causes of death in a group of patients with schizophrenia can be attributed to suicides and compared with the general population, patients with schizophrenia have an 8.5-fold greater suicide risk (SR). There is a vital need for accurate and reliable methods to predict the SR among patients with schizophrenia based on biological measures. However, it is unknown whether the suicidal risk in schizophrenia can be related to alterations in spontaneous brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Our study has some limitations. First, although the sample size is limited, it is relatively larger when compared to previous studies [ 1 , 21 , 31 , 50 , 65 ]. A larger sample size should be recruited in the future to replicate and enrich our findings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our study has some limitations. First, although the sample size is limited, it is relatively larger when compared to previous studies [ 1 , 21 , 31 , 50 , 65 ]. A larger sample size should be recruited in the future to replicate and enrich our findings.…”
Section: Discussionmentioning
confidence: 97%
“…Different studies have reported inconsistent results on the effect of GSR on SZ [ 28 30 ]. As far as we know, very few studies reported the effect of GSR on ML of SZ classification [ 31 ]. However, the sample size of that study was limited, and it did not specifically discuss the effect of GSR on SZ classification.…”
Section: Introductionmentioning
confidence: 99%
“…These cognitive deficits, especially those related to working memory, have an impact on executive control, decision making, and higher reasoning skills, which are protective factors against suicidal ideation and attempts [ 53 , 65 ]. Additionally, recent studies on brain dysfunctions have reported reduced neural activity in suicide attempters who were exposed to fMRI (functional magnetic resonance imaging) [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…While disease trait markers, including diagnostic markers, assist early intervention, other biomarkers are also essential: state markers for estimating dynamic changes in response to treatment 13,14 and staging markers for disease prevention or personalising interventions 15 . These biomarkers have been developed separately in some studies 16,17 , and other studies assumed a shared background 1820 . In SSD research, few studies have succeeded in developing state markers using neuroimaging, and for staging markers, there is no consensus on biological staging models 21 .…”
Section: Introductionmentioning
confidence: 99%